Casting down the host of heaven : the rhetoric of ritual failure in the polemic against the host of heaven - Quine, Cat (Oudtestamentische Studiën, Old Testament Studies, 2020)
"In Casting Down the Host of Heaven Cat Quine analyses the ambiguous nature of the Host and explores the role of ritual in the polemic against their worship. Although commonly assumed to be YHWH's divine army, the book reveals their non-military and fluid nature. Quine demonstrates that it was the fluidity of the Host and their roles in the divine realm that permitted the creation of wide-ranging polemic against their worship. Her analysis shows that this polemic was expressed in ritual terms which persuaded its audiences, both ancient and modern, of its legitimacy and authority".